MULTICULTURAL PERSONALITY OF SINGLE SEX SCHOOL ADOLESCENT - Intani, Esty Noorbaiti; Syahril, M. Fiqri; Budiman, Nandang; Ilfiandra, Ilfiandra; Yudha, Eka Sakti (Universitas Pendidikan Indonesia, 2024)
This study aims to provide an overview of the multicultural personality of single sex adolescents of SMA Daarut Tauhiid Boarding Schools Putri. The research used descriptive analysis methods with the help of Microsoft Excel applications and SPSS version 26. The research instrument used the Multicultural Personality Questionnaire (MPQ) measuring instrument made by Van der Zee Van Oudenhoven (2013) with a total of 40 statements measuring 5 aspects of multicultural personality, namely: cultural empathy, social initiative, open-mindedness, emotional stability, and flexibility, data collection using a Likert scale with five alternative answers. The research participants were students of SMA Daarut Tauhiid Boarding School Putri who were teenagers with female gender totalling 150 people. The results showed that single sex school adolescents have a good multicultural personality, while based on aspects of multicultural personality, single sex school adolescents have the highest average in the aspect of cultural empathy, indicating that students already have skills in empathising (understanding and feeling) with the thoughts and feelings of people of different cultures. And the lowest aspect is in the aspect of open mind, indicating that students do not yet have an open and unprejudiced attitude towards different cultural norms and values optimally so that this can be the basis for designing multicultural guidance and counselling programs that can be applied in single sex schools.